China and India : learning from each other : reforms and policies for sustained growth - Changing Economic Structures in China and India: Domestic and Regional Implications (2005 : Beijing, China); Aziz, Jahangir; Dunaway, Steven Vincent; Prasad, Eswar; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This book draws together analysis and insight from high-level policymakers and advisors in both countries, and shows how, for many years, the two countries have cooperated and learned from each other. In addition, the book describes what has (and what has not) worked in each country and offers some concrete suggestions about how each may achieve long-term sustainable development.
Banking sector reform in India / Nachiket Mor, R. Chandrasekar, and Diviya Wahi -- Reforming China's banking system: how much can foreign strategic investment help? / Nicholas Hope and Fred Hu -- Banking system structure in China and India / Luo Ping -- Development of the securities market in India / G.N. Bajpai -- Development of securities markets: the Indian experience / Narendra Jadhav -- Accelerating the external and internal opening up of China's securities industry / Xinghai Fang, Ti Liu, and Donghui Shi -- Domestic financial liberalization and international financial integration: an Indian perspective / Suman Bery and Kanhaiya Singh -- Putting the cart before the horse? Capital account liberalization and exchange rate flexibility in China / Eswar Prasad, Thomas Rumbaugh, and Qing Wang -- Some apparent puzzles for contemporary monetary policy / Rakesh Mohan -- Fiscal policy in China / Steven Dunaway and Annalisa Fedelino -- Labor mobility in China and India: the role of hukou, caste, and community / Arvinder Singh -- Indian economic development and India-China cooperation / Nalin Surie -- India-China economic cooperation / Arvind Virmani.
Selected papers presented at the conference: Changing Economic Structures in China and India: Domestic and Regional Implications, organized by the International Monetary Fund, the China Society for Finance and Banking, and the Stanford Center for International Development, and held in Beijing on Oct. 27-28, 2005.
Editor statement from cover.
Includes bibliographical references.
oif 06/11/15
Loan
Keywords: China -- Economic policy -- Congresses; India -- Economic policy -- Congresses; Banks and banking -- China -- Congresses; Banks and banking -- India -- Congresses; Securities industry -- China -- Congresses; Securities industry -- India -- Congresses; China -- Foreign economic relations -- India -- Congresses; India -- Foreign economic relations -- China -- Congresses